Preparation method of high wear-resistant wood-plastic floor suitable for high-span installation
Patent Information
- Application Number
- CN202610985413.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]上述现有技术分别从增强、界面粘合、冷却定型等单一角度进行了改进,但均未能提供一种系统性解决方案,以同时实现增强骨架与芯层的一体化无缺陷、耐磨层与芯层的高强度结合以及制品的低内应力和高尺寸稳定性
1、本发明通过S1在共挤熔融区实现增强骨架与芯层基体的分子链级缠结,形成无可辨别相界面的界面一体化结构。该结构从根本上消除了常规复合材料的界面弱区,使界面成为载荷有效传递的桥梁而非应力集中源。DMA测试表明界面损耗因子峰半峰宽拓宽15%以上,证实界面形成了更宽厚的分子链段运动受限的过渡层,显著提升了复合材料的抗弯模量和冲击韧性。在600mm跨距、100kg/m2均布载荷条件下,本发明地板的48h跨中挠度仅为1.5mm,而无增强骨架的对比样达8.2mm。
Smart Images

Figure CN122956686A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wood-plastic composite material processing technology, specifically to a method for preparing high-span, high-wear-resistant wood-plastic flooring through co-extrusion integrated reinforcement, online pretreatment with hot mechanical interlocking, and thermal insulation gradient cooling. Background Technology
[0002] Wood-plastic composite (WPC) flooring has become an important material for outdoor landscaping and building paving due to its advantages such as recyclability, corrosion resistance, and ease of processing. In installation scenarios such as boardwalks and elevated platforms, the spacing between the joists often reaches 400-600mm, which is considered high-span installation. Conventional WPC flooring has a low modulus of elasticity (typically 1-3 GPa), and during long-term use, irreversible deflection deformation can occur due to creep and stress relaxation, seriously affecting safety and aesthetics.
[0003] An effective way to improve the flexural stiffness of wood-plastic composite flooring is to introduce a continuous fiber-reinforced skeleton. Existing technologies include methods that introduce fiber bundles into the melting zone of a co-extrusion die to achieve integrated co-extrusion of the reinforcement and the matrix. However, these methods only reach the macroscopic composite level. The bonding between the fiber and the thermoplastic matrix relies on conventional fiber impregnation agents and mechanical interlocking. Under dynamic loads or thermal cycling conditions, there is a risk of the initiation and expansion of microscopic gaps at the interface, which can be observed under a scanning electron microscope as a clear phase boundary between the fiber and the matrix.
[0004] Existing technologies also include solutions that incorporate a built-in reinforcing skeleton and hot-press a wear-resistant layer to form a mechanical interlock. This method uses hot pressing to partially embed the wear-resistant layer material into the core layer surface, improving interfacial bonding to some extent. However, this method does not perform any pretreatment on the core layer surface; the embedding process relies solely on the physical force of hot pressing, resulting in limited interlocking depth and density. Other existing technologies disclose a method of hot-pressing a wear-resistant layer after corona treatment of the core layer surface, but this pretreatment is an offline operation, failing to utilize the residual heat of the extruded core layer and the high activity of the semi-molten surface.
[0005] Furthermore, for multi-layered products containing a high-modulus reinforcing skeleton and a wear-resistant surface layer, the differences in the coefficients of thermal expansion and modulus of the materials in each layer mean that ordinary single-rate cooling will accumulate significant thermal stress inside the product, especially at the interlayer interfaces. Existing thermal insulation and shaping equipment is mainly designed for ordinary co-extruded flooring and does not address the cooling problem of such highly heterogeneous composites.
[0006] The aforementioned existing technologies have made improvements from individual perspectives such as reinforcement, interfacial bonding, and cooling and shaping, but none of them provide a systematic solution to simultaneously achieve defect-free integration of the reinforcing skeleton and core layer, high-strength bonding between the wear-resistant layer and the core layer, and low internal stress and high dimensional stability of the product. These three properties are indispensable, especially in high-span installation scenarios. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing high-wear-resistant wood-plastic composite flooring suitable for high-span installations, thereby simultaneously solving the three mutually restrictive technical problems mentioned above. The method utilizes the high-temperature and high-pressure environment of the co-extrusion melting zone to achieve molecular chain-level integration of the reinforcing skeleton and matrix (S1); utilizes the residual heat from extrusion and the surface activity of the semi-molten state to achieve online synergy between pretreatment and thermal mechanical interlocking (S2); and designs a gradient cooling system of rapid cooling-insulation-slow cooling for the thermal stress characteristics of the multilayer composite (S3). These three steps are interconnected, ultimately resulting in a high-performance flooring with defect-free interfaces, strong bonding, and low internal stress.
[0008] The technical solution of the present invention is as follows: A method for preparing highly wear-resistant wood-plastic composite flooring suitable for high-span installation, comprising the following steps: S1: Wood-plastic composite material raw material is extruded through a co-extrusion die to form a core layer. During the extrusion process, a continuous reinforcing skeleton is simultaneously formed inside the core layer. The material of the reinforcing skeleton and the material of the core layer undergo molecular chain diffusion and entanglement in the melting zone of the co-extrusion die to form an integrated interfacial structure with no indistinguishable phase interface between the reinforcing skeleton fiber and the core layer matrix. The reinforcing skeleton extends continuously along the length direction of the core layer. S2: After extrusion in step S1 and before cooling and shaping, the surface of the core layer to be composited is pretreated with corona or plasma. Then, immediately when the surface temperature after pretreatment is in the range of 80-120℃, the wear-resistant layer material is applied to the surface and a pressure of 0.2-0.8MPa is applied to allow the wear-resistant layer material to partially penetrate into the surface of the core layer, forming a mechanical interlock interface layer (hereinafter referred to as the interlock layer) with a thickness of 0.1-0.5mm. S3: The composite obtained in step S2 is subjected to synchronous cooling and shaping. The synchronous cooling and shaping adopts a gradient cooling process. The gradient cooling process includes a first cooling stage with a first cooling rate, a heat preservation stage, and a second cooling stage with a second cooling rate in sequence. The heat preservation stage keeps the composite at a temperature of 40-60°C. The first cooling rate is higher than the second cooling rate, and the first cooling rate is at least 5°C / min higher than the second cooling rate.
[0009] The following provides further explanation of each step.
[0010] In step S1, the continuous reinforcing skeleton is introduced into the high-temperature, high-pressure melting zone of the co-extrusion die. The pressure inside the die is ≥8MPa, and the temperature is 15-25℃ higher than the melting point of the wood-plastic matrix. The length of the melting zone of the co-extrusion die is ≥20D (D is the characteristic dimension of the flow channel), and the residence time of the melt in the melting zone is ≥30 seconds, ensuring that the polymer chain segments have sufficient time to diffuse into the interior of the reinforcing skeleton and physically entangle with the molecular chains on the fiber surface. The "interface integrated structure with indistinguishable phase interfaces" refers to the presence of indistinguishable clear boundaries or cracks between the reinforcing skeleton fibers and the core matrix when observing the brittle fracture surface of the composite under a 5000x scanning electron microscope, presenting a blurred transition of molecular chain entanglement layers. This structure makes the interface no longer a source of stress concentration, but a bridge for effective load transfer. As a preferred objective criterion, the gray value line scanning curve across the interface in the SEM image can be extracted. If the transition width of the gray value from the fiber region to the matrix region is ≥0.5μm and there is no steep step, it is determined to be an interface integrated structure with indistinguishable phase interfaces.
[0011] In step S2, the surface of the freshly extruded core layer is first pretreated with corona or plasma. "Immediately" means that the pretreatment and pressing stations are performed online continuously, and the wear-resistant layer is applied before the surface activity generated by the pretreatment significantly decays. Preferably, the interval between the two stations does not exceed 10 seconds. The wear-resistant layer material is applied and pressurized within a surface temperature window of 80-120°C. This temperature range is higher than the glass transition temperature of the matrix material but lower than its melting temperature. The core layer surface is in the high-elasticity / viscous flow transition zone, exhibiting a certain degree of fluidity. Under a pressure of 0.2-0.8 MPa, the wear-resistant layer melt can penetrate into the pretreated and etched micropores, forming an interlocking layer with an anchoring depth of 0.1-0.5 mm. The penetration depth is determined by pressure, temperature, melt viscosity, and action time, and can be controlled by adjusting the pressure and gap of the pressure rollers.
[0012] In step S3, the composite undergoes a gradient cooling process of rapid cooling, heat preservation, and slow cooling. The rapid cooling in the first stage quickly cools and solidifies the composite surface, preventing deformation of the wear-resistant layer. Subsequently, a heat preservation stage of 40-60°C is entered. This temperature range is near the heat distortion temperature of the matrix material, allowing sufficient time for the molecular chain segments to undergo conformational adjustment and stress relaxation, eliminating internal stress caused by rapid cooling. The final slow cooling stage causes the entire product to shrink slowly, avoiding interlayer thermal stress caused by the difference in thermal expansion coefficients between the core layer and the wear-resistant layer.
[0013] As a further preferred embodiment of step S1, the continuous reinforcing skeleton may be selected from a continuous fiber bundle extending parallel to the length direction of the core layer, a fiber mesh fabric distributed in a grid pattern within the cross-section of the core layer, or an X-shaped reinforcing bracket spaced apart along the length direction of the core layer; the material of the reinforcing skeleton is selected from at least one of glass fiber, carbon fiber, basalt fiber, or metal wire; the volume of the reinforcing skeleton accounts for 5-20% of the total volume of the core layer.
[0014] As a further optimization of the reinforcing skeleton distribution, the reinforcing skeleton formed in step S1 can be non-uniformly distributed within the core layer cross-section. In the thickness direction, the area density of the reinforcing skeleton near the upper surface of the core layer is 1.2-2.0 times that of the reinforcing skeleton near the lower surface of the core layer. The area density is defined as the percentage of the cross-sectional area of the reinforcing skeleton to the total area of the layer within a 0.5 mm distance from the upper and lower surfaces. This gradient distribution can utilize the reinforcing material more efficiently and improve the high-span bending stiffness.
[0015] As a further preferred embodiment of step S2, the wear-resistant layer raw material may further include an interface modifier. The interface modifier is a mechanically mixed compound of hyperbranched polyester lubricant and titanate coupling agent, with a mass ratio of 1:0.5-2, and the interface modifier accounts for 0.5-3% of the total mass of the wear-resistant layer raw material. This compound can improve the melt flowability of the wear-resistant layer, promote penetration, and react with the surface active groups of the core layer, further enhancing the interface.
[0016] As a further optimization of the material matching relationship, the tensile elastic modulus E1 of the reinforcing skeleton in step S1 and the tensile elastic modulus E2 of the wear-resistant layer in step S2 satisfy: E1 / E2=0.8-1.5, and the elongation of the reinforcing skeleton is... With respect to the elongation of the wear-resistant layer satisfy: This ensures that when the floor is bent, the deformation of the reinforcing frame and the wear-resistant layer is coordinated, avoiding the concentration of interlayer shear stress caused by excessive stiffness differences.
[0017] Preferably, the residence time of the molten zone in the co-extrusion die in step S1 is... The following relationship must be satisfied: ≥5× ,in The term refers to the terminal relaxation time of the thermoplastic polymer in the wood-plastic substrate raw material at the co-extrusion processing temperature.
[0018] As a further optimization of the raw material composition, the wood-plastic composite material raw material in step S1 may contain 20-40 parts by weight of recycled waste fiber material. The recycled waste fiber material is pre-treated with plasma at a power of 200-500W for 30-120s to introduce hydroxyl or carboxyl active functional groups onto its surface. In addition, the wear-resistant layer raw material in step S2 contains a hydroxyl-terminated polybutadiene-grafted maleic anhydride copolymer, wherein the number average molecular weight of the hydroxyl-terminated polybutadiene is 1000-5000. The copolymer forms a chemical bond by reacting with the hydroxyl or carboxyl groups on the surface of the recycled waste fiber through its maleic anhydride groups.
[0019] As a further optimization of step S2, while applying the wear-resistant layer material, a three-dimensional embossing can be formed on the surface of the wear-resistant layer by pressing with a patterned roller. The temperature of the patterned roller is controlled at 100-150℃, and the pressure is controlled at 0.3-1.0MPa; the embossing depth is 0.2-0.8mm. Furthermore, the raised portions of the embossing correspond to the distribution positions of the reinforcing skeleton inside the core layer in the thickness direction of the floor, with an offset tolerance within ±2mm.
[0020] As a further supplement to the above preparation method, step S4 may also be included: forming an installation positioning structure on the lower surface of the obtained floor corresponding to the position of the reinforcing skeleton, the installation positioning structure including raised positioning strips spaced apart along the length direction of the floor, the spacing between adjacent raised positioning strips being 300-600mm, the position of the raised positioning strips corresponding to the reinforcing nodes of the reinforcing skeleton in the length direction, and the offset tolerance being within ±5mm.
[0021] A highly wear-resistant wood-plastic composite flooring suitable for high-span installation, prepared by any of the above methods, has the following structural features: (i) At the interface between the reinforcing skeleton fiber and the core matrix, there exists a molecular chain entanglement transition layer with a thickness of 0.5-2 μm. This transition layer has no discernible clear phase boundary under a 5000x scanning electron microscope, and the loss factor measured by dynamic mechanical analysis is... The peak half-peak width is at least 15% wider than that of the control sample which uses the same raw materials but does not introduce a reinforcing skeleton through co-extrusion; (ii) Between the wear-resistant layer and the core layer, a mechanically interlocking interface layer with a depth of 0.1-0.5 mm is formed. The cross-sectional microstructure shows that the wear-resistant layer material penetrates into the micropores on the surface of the core layer in a finger-like or nail-like manner, forming a physical anchoring density of not less than 100 anchors / mm. 2 ; (iii) The residual stress inside the floor section does not exceed 1.5 MPa.
[0022] Furthermore, the flooring simultaneously meets the following performance indicators: (a) According to ASTM D4060 standard, the Taber abrasion value is ≤50mg / 1000r; (b) According to ASTM D903 standard, the peel strength between the wear-resistant layer and the core layer is ≥3.2 N / mm; (c) After treatment at 80℃ for 48 hours, the length change rate is ≤0.1% according to GB / T 24508 standard; (d) Notched impact strength of simply supported beam ≥ 25 kJ / m 2 .
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention achieves molecular chain-level entanglement between the reinforcing skeleton and the core matrix in the co-extrusion melt zone via S1, forming an interfacial integrated structure with indistinguishable phase interfaces. This structure fundamentally eliminates the interfacial weak zones of conventional composite materials, making the interface a bridge for effective load transfer rather than a source of stress concentration. DMA testing shows that the half-maximum width of the interfacial loss factor peak is broadened by more than 15%, confirming the formation of a thicker transition layer with restricted molecular chain movement at the interface, significantly improving the flexural modulus and impact toughness of the composite material. (Note: The last sentence about 600mm span and 100kg / m is unrelated and appears to be a separate, incomplete thought.) 2 Under uniformly distributed load conditions, the mid-span deflection of the floor of the present invention is only 1.5 mm over 48 hours, while the comparative sample without a reinforced frame has a deflection of 8.2 mm.
[0024] 2. This invention overcomes the technical bias of pre-cooling followed by processing by directly pre-treating the core layer surface after extrusion using S2, and immediately applying the wear-resistant layer during the hot state window of 80-120℃. Utilizing the high activity of the core layer surface in the high-elasticity / viscous flow transition zone, the wear-resistant layer melt can penetrate the pre-treated etched micropores, forming a mechanically interlocked layer with a depth of 0.1-0.5mm and an anchoring density of not less than 100 interlocking points / mm. 2 The peel strength of the abrasion layer of the resulting flooring can reach over 3.2 N / mm, which is significantly better than the 2.6 N / mm of the untreated control sample.
[0025] 3. This invention employs a rapid cooling-insulation-slow cooling gradient cooling process (S3). First, rapid cooling locks in the interface formed by S1 and S2. Then, sufficient stress relaxation is achieved during the 40-60℃ insulation stage. Finally, slow cooling enables uniform shrinkage. This three-stage gradient cooling process controls the residual stress in the product's cross-section to below 1.5 MPa, while the residual stress of the comparative sample cooled at a single rate reaches 3-5 MPa. Correspondingly, the length change rate of the flooring of this invention under 80℃ / 48h conditions is ≤0.1%, significantly better than the 0.18% of the comparative sample in terms of dimensional stability.
[0026] 4. There is a synergistic effect among the three steps of the present invention. The reinforcing skeleton formed in S1 provides dimensional stability for the high-temperature operation of S2, enabling S2 to be safely carried out within the temperature window of 80-120℃, which is considered a danger zone in conventional processes; the interlocking layer formed in S2 provides a high-strength interface for the insulation stress relaxation in S3, preventing interlayer cracking during the insulation process; the gradient cooling in S3 solidifies the results of the first two steps and eliminates internal stress. Comparative experiments show that the comparative example lacking both S2 and S3 has a peel strength of only 2.0 N / mm and a length change rate as high as 0.25%, with a performance degradation exceeding the sum of the losses from missing a single step, demonstrating the significant effect of the three-step synergy.
[0027] 5. The flooring produced by the method of this invention simultaneously meets the following requirements: Taber abrasion ≤ 50 mg / 1000 r, peel strength ≥ 3.2 N / mm, length change rate at 80℃ / 48h ≤ 0.1%, and notched impact strength of simply supported beam ≥ 25 kJ / m. 2 Four performance indicators can meet the stringent requirements for the comprehensive performance of materials in high-span paving scenarios with a keel spacing of 400-600mm. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the process flow for the preparation method of the present invention. Detailed Implementation
[0029] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but these embodiments are only used to explain the present invention and are not intended to limit its scope.
[0030] Raw material description: Hyperbranched polyester lubricant: hydroxyl value 50-80 mgKOH / g, number average molecular weight 2000-5000; titanate coupling agent: Isopropyl tris(isostearoyl) titanate type, titanium content ≥8%; hydroxyl-terminated polybutadiene-grafted maleic anhydride copolymer: Maleic anhydride grafting rate 1.5-3.0wt%, hydroxyl value 20-40mgKOH / g; Plasma processing equipment: radio frequency power supply frequency 13.56MHz or 20kHz, processing atmosphere is air or oxygen.
[0031] Example 1 Reference Figure 1 The raw material formula for wood-plastic composite substrate (by weight): 60 parts polyvinyl chloride (SG-5), 30 parts poplar wood powder (80 mesh), 4 parts calcium zinc stabilizer, 1.5 parts stearic acid lubricant, and 0.5 parts PE wax are mixed in a high-speed mixer to 110°C and then cooled.
[0032] Step S1: Add the above mixture to a twin-screw extruder. The barrel temperature is 160-180℃. Extrude the core layer through a co-extrusion die. Continuous glass fiber bundles (E-glass, 2400 tex) are introduced into the die's melting zone through reinforcing skeleton inlet 3. The co-extrusion die's melting zone length is 150 mm (flow channel characteristic dimension D = 6 mm, length-to-diameter ratio 25:1), melt pressure is 10 MPa, temperature is 175℃, and melt residence time is approximately 45 seconds. The reinforcing skeleton accounts for 15% of the volume, the extrusion speed is 1.0 m / min, and the core layer cross-sectional dimensions are 145 mm × 25 mm.
[0033] Step S2: After the core layer is demolded, it undergoes a plasma treatment device (power frequency 20kHz, power 300W, treatment distance 2mm, time 5s). The center distance between the plasma treatment device and the pressure roller is 0.8m, corresponding to an interval of 4.8 seconds. At this time, the surface temperature of the core layer is approximately 100±5℃. The wear-resistant layer material (formula: 100 parts PVC resin, 20 parts alumina (α-Al2O3, 5μm), 2 parts hyperbranched polyester / titanium ester coupling agent compound (mass ratio 1:1)) is plasticized by a single-screw extruder and applied to the upper surface of the core layer, with a pressure roller pressure of 0.5MPa. Simultaneously, a patterned roller (temperature 120℃, pressure 0.6MPa) presses a wood grain texture with a depth of 0.5mm onto the surface of the wear-resistant layer. Observation of the finished product cross-section shows that the wear-resistant layer material penetrates into the surface of the core layer in a finger-like pattern, the average thickness of the interlocking layer is 0.32mm, and the anchor point density is approximately 120 points / mm. 2 The grayscale transition width is 1.2μm.
[0034] Step S3: The composite enters the gradient cooling and shaping device and passes through the first cooling zone (5℃ cold air, cooling rate of about 12℃ / min), the heat preservation zone (hot air temperature of 50±2℃, held for 3 minutes), and the second cooling zone (20℃ air cooling, cooling rate of about 4℃ / min) in sequence to solidify and obtain the finished floor.
[0035] Performance: Taber abrasion loss 45 mg / 1000 r, peel strength 3.5 N / mm, length change rate at 80℃ / 48 h 0.08%, notched impact strength of simply supported beam 28 kJ / m 2 The residual stress is 1.1 MPa.
[0036] Example 2 Unlike Example 1: In step S1, recycled cotton fibers (pretreated with plasma, 400W power, 60s time) were used to replace part of the wood flour, with a dosage of 25 parts; the reinforcing skeleton was changed to carbon fiber mesh (T300 grade, 10% by volume), and a thickness gradient distribution was achieved through a flow divider, with an upper surface area density of 18.5% and a lower surface area density of 12.3%, a ratio of 1.5. In step S2, 5 parts of hydroxyl-terminated polybutadiene-grafted maleic anhydride copolymer (Mn=3000) were added to the wear-resistant layer raw material, the pressure of the pressure roller was 0.8MPa, and the thickness of the interlocking layer was 0.4mm. In step S3, the heat preservation stage was maintained at 40℃ for 4 minutes. The rest was the same as in Example 1.
[0037] Performance: Abrasion loss 42mg / 1000r, peel strength 3.8N / mm, length change rate 0.06%, impact strength 26kJ / m 2 The residual stress is 1.2 MPa.
[0038] Example 3 Unlike Example 1: In step S1, the reinforcing skeleton is an X-shaped metal wire support (304 stainless steel, wire diameter 0.5mm, cross node spacing 80mm, volume percentage 8%), introduced through co-extrusion. Under high temperature and pressure in the molten zone, the PVC melt fully wets the surface of the metal wire, with a grayscale transition width of 0.9μm. In step S2, the pretreatment uses corona discharge (power 200W) at a surface temperature of 110℃; in step S3, the first cooling rate is 15℃ / min, the holding temperature is 55℃, and the second cooling rate is 5℃ / min. In step S4, raised positioning strips are milled on the lower surface of the finished floor, spaced 400mm apart, and aligned with the cross nodes of the X-shaped support (longitudinal deviation ±3mm).
[0039] The floor of this embodiment and Comparative Example 7 (where the raised positioning strips are randomly offset, with an average deviation of 50mm from the reinforcing nodes) are placed on joists spaced 500mm apart, with a uniformly distributed load of 100kg / m². 2 After 48 hours: The mid-span deflection in this embodiment is 1.3 mm, while the deflection in Comparative Example 7 is 2.8 mm.
[0040] Performance: Abrasion loss 44 mg / 1000 r, peel strength 3.4 N / mm, length change rate 0.08%, impact strength 27 kJ / m 2 The residual stress is 1.3 MPa.
[0041] Examples 4-5 The values at the 5% and 20% volumetric weight ratios of the reinforcing skeleton were verified respectively. Example 4 (5%): abrasion loss 46 mg / 1000 r, peel strength 3.3 N / mm, length change rate 0.09%, impact strength 26 kJ / m 2Example 5 (20%): Abrasion loss 48 mg / 1000 r, peel strength 3.4 N / mm, length change rate 0.07%, impact strength 30 kJ / m 2 The rest is the same as in Example 1.
[0042] Example 6 Step S1: The reinforcing skeleton is made of E-glass fiber (E1=72GPa). =2.5%). Step S2: The wear-resistant layer uses modified polyvinyl chloride (with 5 parts of acrylate toughening agent added), E2=60GPa, =2.0%. E1 / E2=1.2, Comparative Example 6: The wear-resistant layer is made of untoughened polyvinyl chloride, E2=80GPa. =1.2%, Three-point bending DIC method measurements showed that the maximum interlayer shear strain in Example 6 was 0.8%, while that in Comparative Example 6 was 2.0%.
[0043] Performance: Example 6: Abrasion loss 44 mg / 1000 r, peel strength 3.6 N / mm, length change rate 0.07%, impact strength 29 kJ / m 2 Comparative Example 6: Abrasion loss 46 mg / 1000 r, peel strength 3.4 N / mm, length change rate 0.08%, impact strength 23 kJ / m 2 .
[0044] Examples 7-8 The area density ratios of 1.2 and 2.0 were verified separately. Example 7 (ratio 1.2): 13.8% for the upper surface and 11.5% for the lower surface; the flexural stiffness over a 600mm span was 12% higher than that of the uniformly distributed sample. Example 8 (ratio 2.0): 20.0% for the upper surface and 10.0% for the lower surface; the stiffness was increased by 35%. The rest was the same as in Example 2.
[0045] Example 9 The embossing depths were verified at 0.2 mm (pattern roller temperature 100℃, pressure 0.3 MPa) and 0.8 mm (pattern roller temperature 150℃, pressure 1.0 MPa). At 0.2 mm: abrasion loss 48 mg / 1000 r, peel strength 3.3 N / mm. At 0.8 mm: abrasion loss 43 mg / 1000 r, peel strength 3.2 N / mm. The rest was the same as in Example 1.
[0046] Example 10 Verification of the cooling rate difference at a 5℃ / min threshold: First cooling rate 8℃ / min, held at 50℃ for 3 minutes; second cooling rate 3℃ / min. Performance: Abrasion wear 46mg / 1000r, peel strength 3.3N / mm, length change rate 0.09%, impact strength 27kJ / m. 2 The rest is the same as in Example 1.
[0047] Example 11 Step S1: The wood-plastic composite substrate contains 25 parts of recycled cotton fiber (plasma pretreatment, power 400W, time 60s). Step S2: The wear-resistant layer contains 5 parts of hydroxyl-terminated polybutadiene-grafted maleic anhydride copolymer (Mn=3000).
[0048] Comparative Example 11a: Recycled cotton fibers were not subjected to plasma treatment. Comparative Example 11b: The abrasion-resistant layer did not contain hydroxyl-terminated polybutadiene-grafted maleic anhydride copolymer.
[0049] Example 11 showed a peel strength of 3.8 N / mm, compared to 3.1 N / mm for Comparative Example 11a and 3.0 N / mm for Comparative Example 11b. Infrared spectroscopy confirmed that the interface layer of Example 11 had a strength of 1735 cm⁻¹. -1 A characteristic absorption peak for ester bonds appears at [location].
[0050] Example 11 Integrity Performance: Abrasion loss 43 mg / 1000 r, peel strength 3.8 N / mm, length change rate 0.06%, impact strength 27 kJ / m 2 .
[0051] Example 12 The wood-plastic composite substrate was changed to HDPE substrate. The formulation consisted of 50 parts HDPE, 40 parts poplar wood powder, 5 parts MAPE, and 2 parts lubricant. Step S1: Barrel temperature 150-170℃, melting zone temperature 165℃, reinforcing skeleton basalt fiber bundles (3000 tex), volume percentage 12%, residence time approximately 6 seconds. Step S2: Surface temperature 88±5℃, after corona pretreatment, a PE-based wear-resistant layer (containing 15 parts alumina) was applied. Step S3: Insulation temperature 45℃. SEM grayscale transition width 1.0μm. Performance: Abrasion loss 48mg / 1000r, peel strength 3.3N / mm, length change rate 0.08%, impact strength 34kJ / m. 2 The residual stress is 1.0 MPa.
[0052] Example 13 The wood-plastic composite substrate was changed to PP substrate. The formula consisted of 55 parts PP, 35 parts poplar wood powder, 5 parts MAPP, and 2 parts lubricant. Step S1: Barrel temperature 170-190℃, melting zone temperature 185℃, reinforcing skeleton made of glass fiber bundles (2400 tex), volume percentage 12%, residence time approximately 5 seconds. Step S2: Surface temperature 90±5℃, after plasma pretreatment, a PP-based wear-resistant layer (containing 15 parts alumina) was applied. Step S3: Holding temperature 50℃. SEM grayscale transition width 1.1μm. Performance: Abrasion wear 46mg / 1000r, peel strength 3.5N / mm, length change rate 0.07%, impact strength 31kJ / m. 2 The residual stress is 1.1 MPa.
[0053] Based on Example 1, when the interface modifier dosage is 0.5%, the abrasion loss is 46 mg / 1000 r and the peel strength is 3.3 N / mm. When the dosage is 3%, the abrasion loss is 42 mg / 1000 r and the peel strength is 3.7 N / mm. Both meet the performance indicators.
[0054] Comparative Example 1 Step S3 involves continuous cooling to room temperature at a single cooling rate of 5℃ / min. Performance: abrasion loss 48mg / 1000r, peel strength 2.9N / mm, length change rate 0.18%, impact strength 22kJ / m. 2 The residual stress is 3.5 MPa.
[0055] Comparative Example 2 Step S2 does not involve plasma pretreatment; the wear-resistant layer is directly hot-pressed. Performance: abrasion wear 46 mg / 1000 r, peel strength 2.6 N / mm, length change rate 0.12%, impact strength 24 kJ / m. 2 The residual stress is 3.0 MPa.
[0056] Comparative Example 3 Step S1 involves direct extrusion of the core layer without introducing a reinforcing skeleton. Performance: abrasion loss 50 mg / 1000 r, peel strength 3.5 N / mm, length change rate 0.10%, impact strength 18 kJ / m. 2 600mm span, 100kg / m 2 The deflection was 8.2 mm after 48 hours of load.
[0057] Comparative Example 4 Step S2 has no pretreatment; Step S3 is a single cooling rate of 5℃ / min. Performance: abrasion loss 47mg / 1000r, peel strength 2.0N / mm, length change rate 0.25%, impact strength 20kJ / m. 2 The residual stress is 4.2 MPa.
[0058] Comparative Example 5 In Example 1 and Comparative Example 3, the floor was placed on a 600mm simply supported surface with a uniformly distributed load of 100kg / m. 2 After 48 hours, the mid-span deflection was 1.5 mm in Example 1 and 8.2 mm in Comparative Example 3.
[0059] Comparative Example 8 Step S3: First cooling rate 7℃ / min, holding temperature 50℃; second cooling rate 4℃ / min, rate difference 3℃ / min. Performance: Abrasion wear 47mg / 1000r, peel strength 3.1N / mm, length change rate 0.14%, impact strength 24kJ / m. 2 The residual stress is 2.6 MPa. All three performance indicators fail to meet the standards.
[0060] Performance Test Summary Table All embodiments meet the following requirements: abrasion ≤ 50 mg / 1000 r, peel strength ≥ 3.2 N / mm, length change rate ≤ 0.1%, and impact strength ≥ 25 kJ / m. 2 .
[0061] Criteria for selecting key parameters in this invention The volumetric reinforcement ratio should be 5-20%: below 5%, the reinforcement effect is not significant; above 20%, dispersion is difficult and impact strength decreases. Surface temperature window 80-120℃: Below 80℃, molecular chain segments are frozen, and the pretreatment effect is reduced; above 120℃, the matrix modulus is too low, and pressure can easily lead to cross-sectional distortion. Interlocking layer thickness 0.1-0.5mm: less than 0.1mm results in insufficient anchoring effect, while more than 0.5mm affects the integrity of the core layer structure; Insulation temperature: 40-60℃; below 40℃, stress relaxation is insufficient; above 60℃, it may cause secondary softening and deformation of the product. In Examples 1 (50℃), 2 (40℃), and 3 (55℃), the residual stress is ≤1.5MPa. Cooling rate difference ≥ 5℃ / min: Comparative Example 8 (3℃ / min) failed to meet the three indicators, and 5℃ / min is the critical value; Area density ratio 1.2-2.0: Below 1.2 times the gradient effect is not significant, and above 2.0 times the lower surface fiber is too low, which leads to a decrease in impact strength; The dosage of the interface modifier is 0.5-3%: below 0.5%, the modification effect is not significant, and above 3%, the processing performance decreases; Embossing depth 0.2-0.8mm: less than 0.2mm, the texture durability is insufficient; more than 0.8mm, it may damage the continuity of the wear-resistant layer.
[0062] The above description is merely a preferred embodiment of the present invention and does not limit the scope of patent protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing highly wear-resistant wood-plastic composite flooring suitable for high-span installation, characterized in that, Includes the following steps: S1: Wood-plastic composite material raw material is extruded through a co-extrusion die to form a core layer. During the extrusion process, a continuous reinforcing skeleton is simultaneously formed inside the core layer. The material of the reinforcing skeleton and the material of the core layer undergo molecular chain diffusion and entanglement in the melting zone of the co-extrusion die to form an integrated interfacial structure with no indistinguishable phase interface between the reinforcing skeleton fiber and the core layer matrix. The reinforcing skeleton extends continuously along the length direction of the core layer. S2: After extrusion in step S1 and before cooling and shaping, the surface of the core layer to be composited is pretreated with corona or plasma. Then, immediately when the surface temperature after pretreatment is in the range of 80-120℃, the wear-resistant layer material is applied to the surface and a pressure of 0.2-0.8MPa is applied to allow the wear-resistant layer material to partially penetrate into the surface of the core layer, forming a mechanically interlocked interface layer with a thickness of 0.1-0.5mm. S3: The composite obtained in step S2 is subjected to synchronous cooling and shaping. The synchronous cooling and shaping adopts a gradient cooling process, which sequentially includes a first cooling stage with a first cooling rate, a heat preservation stage, and a second cooling stage with a second cooling rate. In the heat preservation stage, the composite is held at a temperature of 40-60°C. The first cooling rate is higher than the second cooling rate, and the first cooling rate is at least 5°C / min higher than the second cooling rate, so that the core layer, the reinforcing skeleton, and the wear-resistant layer are cured to form an integral structure.
2. The method for preparing a high-wear-resistant wood-plastic flooring suitable for high-span installation according to claim 1, characterized in that, The continuous reinforcing skeleton in step S1 is selected from at least one of the following structures: a continuous fiber bundle extending parallel to the length direction of the core layer, a fiber mesh fabric distributed in a grid pattern in the cross-section of the core layer, or an X-shaped reinforcing bracket spaced apart along the length direction of the core layer; the material of the reinforcing skeleton is selected from at least one of glass fiber, carbon fiber, basalt fiber or metal wire, and the volume of the reinforcing skeleton accounts for 5-20% of the total volume of the core layer.
3. The method for preparing a high wear-resistant wood-plastic flooring suitable for high-span installation according to claim 2, characterized in that, The reinforcing skeleton formed in step S1 is non-uniformly distributed within the cross-section of the core layer. The distribution density of the reinforcing skeleton is higher in the central region of the core layer than in the edge region. Furthermore, in the thickness direction of the core layer, the area density of the reinforcing skeleton near the upper surface of the core layer is 1.2-2.0 times that of the reinforcing skeleton near the lower surface of the core layer. The area density is defined as the percentage of the cross-sectional area of the reinforcing skeleton to the total area of the layer within a 0.5 mm distance from the upper and lower surfaces.
4. The method for preparing a high wear-resistant wood-plastic flooring suitable for high-span installation according to claim 1, characterized in that, The wear-resistant layer material in step S2 also includes an interface modifier, which is a mechanically mixed compound of hyperbranched polyester lubricant and titanate coupling agent with a mass ratio of 1:0.5-2, and the interface modifier accounts for 0.5-3% of the total mass of the wear-resistant layer material.
5. The method for preparing a high-wear-resistant wood-plastic flooring suitable for high-span installation according to claim 1, characterized in that, The mechanical interlock interface layer formed in step S2 has the following structural features: Its cross-sectional microstructure shows that the wear-resistant layer material penetrates into the micropores on the surface of the core layer in a finger-like or nail-like manner, forming a physical anchoring density of not less than 100 particles / mm². 2 .
6. The method for preparing a high-wear-resistant wood-plastic flooring suitable for high-span installation according to claim 1, characterized in that, The tensile elastic modulus E1 of the reinforcing skeleton in step S1 and the tensile elastic modulus E2 of the wear-resistant layer in step S2 satisfy: E1 / E2 = 0.8-1.5, and the elongation of the reinforcing skeleton is... With respect to the elongation of the wear-resistant layer satisfy: .
7. The method for preparing a high-wear-resistant wood-plastic flooring suitable for high-span installation according to claim 1, characterized in that, The wood-plastic composite material raw material in step S1 comprises 20-40 parts by weight of recycled waste fiber material. The recycled waste fiber material is pre-treated with plasma at a power of 200-500W for 30-120s before being added to the wood-plastic composite material raw material, so as to introduce hydroxyl or carboxyl active functional groups on its surface. In addition, the wear-resistant layer raw material in step S2 comprises hydroxyl-terminated polybutadiene-grafted maleic anhydride copolymer, wherein the number average molecular weight of the hydroxyl-terminated polybutadiene is 1000-5000. The copolymer forms a chemical bond by chemically reacting with the hydroxyl or carboxyl groups on the surface of the recycled waste fiber through its maleic anhydride groups.
8. The method for preparing a high-wear-resistant wood-plastic flooring suitable for high-span installation according to claim 1, characterized in that, In step S2, while applying the wear-resistant layer material, a three-dimensional embossing is formed on the surface of the wear-resistant layer by pressing with a patterned roller. The temperature of the patterned roller is controlled at 100-150℃, and the pressure is controlled at 0.3-1.0MPa. The depth of the embossing is 0.2-0.8mm, and the raised part of the embossing corresponds to the distribution position of the reinforcing skeleton inside the core layer in the thickness direction of the floor, and the offset tolerance of the corresponding position is within ±2mm.
9. A method for preparing a high-wear-resistant wood-plastic composite flooring suitable for high-span installation according to claim 1, characterized in that, The preparation method further includes step S4 after step S3: forming an installation positioning structure on the lower surface of the obtained floor corresponding to the position of the reinforcing skeleton. The installation positioning structure includes raised positioning strips spaced apart along the length direction of the floor. The spacing between adjacent raised positioning strips is 300-600mm. The position of the raised positioning strips corresponds to the reinforcing node of the reinforcing skeleton in the length direction, and the longitudinal offset tolerance of the corresponding position is within ±5mm.
10. A highly wear-resistant wood-plastic composite flooring suitable for high-span installation, characterized in that, The floor is prepared by the method according to any one of claims 1-9, and the floor has the following structural features: (i) In the interfacial region between the reinforcing skeleton fiber and the core matrix, there is a molecular chain entanglement transition layer with a thickness of 0.5-2 μm. This transition layer has no discernible clear phase boundary under a 5000x scanning electron microscope, and the half-maximum width of the loss factor Tanδ peak measured by dynamic mechanical analysis is at least 15% wider than that of the control sample which uses the same raw material but does not introduce the reinforcing skeleton through co-extrusion. (ii) Between the wear-resistant layer and the core layer, a mechanically interlocking interface layer with a depth of 0.1-0.5 mm is formed. The cross-sectional microstructure shows that the wear-resistant layer material penetrates into the micropores on the surface of the core layer in a finger-like or nail-like manner, forming a physical anchoring density of not less than 100 anchors / mm. 2 ; (iii) The residual stress inside the floor section does not exceed 1.5 MPa; Furthermore, the flooring simultaneously meets the following performance indicators: (a) According to ASTM D4060 standard, the Taber abrasion value is ≤50mg / 1000r; (b) According to ASTM D903 standard, the peel strength between the wear-resistant layer and the core layer is ≥3.2 N / mm; (c) After treatment at 80℃ for 48 hours, the length change rate is ≤0.1% according to GB / T 24508 standard; (d) Notched impact strength of simply supported beam ≥ 25 kJ / m 2 .